In vivo subcellular imaging of tumors in mouse models using a fluorophore‐conjugated anti‐carcinoembryonic antigen antibody in two‐photon excitation microscopy. Issue 10 (October 2014) - Koga, Shigehiro; Oshima, Yusuke; Honkura, Naoki; Iimura, Tadahiro; Kameda, Kenji; Sato, Koichi; Yoshida, Motohira; Yamamoto, Yuji; Watanabe, Yuji; Hikita, Atsuhiko; Imamura, Takeshi
<x xml:space="preserve">Abstract</x> Recently, there has been growing interest in applying fluorescence imaging techniques to the study of various disease processes and complex biological phenomena in vivo. To apply these methods to clinical settings, several groups have developed protocols for fluorescence imaging using antibodies against tumor markers conjugated to fluorescent substances. Although these probes have been useful in macroscopic imaging, the specificity and sensitivity of these methods must be improved to enable them to detect micro‐lesions in the early phases of cancer, resulting in better treatment outcomes. To establish a sensitive and highly specific imaging method, we used a fluorophore‐conjugated anti‐carcinoembryonic antigen (CEA) antibody to perform macroscopic and microscopic in vivo imaging of inoculated cancer cells expressing GFP with or without CEA. Macroscopic imaging by fluorescence zoom microscopy revealed that bio‐conjugation of Alexa Fluor 594 to the anti‐CEA antibody allowed visualization of tumor mass consisting of CEA‐expressing human cancer cells, but the background levels were unacceptably high. In contrast, microscopic imaging using a two‐photon excitation microscope and the same fluorescent antibody resulted in subcellular‐resolution imaging that was more specific and sensitive than conventional imaging using a fluorescence zoom microscope. These results suggest that two‐photon excitation microscopy in conjunction with fluorophore‐conjugated antibodies could be widely adapted to detection of cancer‐specific cell‐surface molecules, both in cancer research and in clinical applications.